Una lezione particolare. Alfredo Puerari e la caduta del fascismo a Cremona - Morandi, Matteo (Studi sulla Formazione/Open Journal of Education, 2021)
The essay presents to the reader, as a possible source for a well-rounded history of the school in Italy during Fascism, the curious Diario di una persona comune (Diary of an ordinary person), written by professor Alfredo Puerari in the aftermath of 25 July 1943 and published immediately after the war on the newspaper of the Ticino Liberal-Radical Party «Il Dovere», in the column Cultura e azione directed by Gianfranco Contini. The writing, which collects the impressions of a teacher of Italian, Latin and Art History of the Liceo Manin in Cremona, active in the ideal resistance to the regime, offers useful elements for the reconstruction of the teaching culture in the dark years of the dictatorship, as well as giving information on the first antifascist meeting organized in the shadow of Torrazzo after the fall of Mussolini.